Troubled by unequal pay rather than low pay: The incentive effects of a top management team pay gap - Yue Xu; Yunguo Liu; Gerald J. Lobo (China Journal of Accounting Research, 2016)
We examine the relationships with firm performance of the internal pay gap among individual members of the top management team (TMT) and the compensation level of TMT members relative to their industry peers. We find that pay gap is positively related to firm performance and that this positive relation is stronger when the TMT pay level is higher than the industry median. However, we do not observe such effects in Chinese state-owned enterprises (SOEs), in which both the executive managerial market and compensation are government-regulated. We also document that cutting central SOE managers' pay level can increase firm value, whereas doing so for local SOE managers has the opposite effect. Our findings have important implications for research on TMT compensation as well as for policy makers considering SOE compensation reform.
Keywords: D23; D82; J31; 650; TMT pay level; Pay gap; Property rights; SOE salary reform